2018
DOI: 10.1136/bmjopen-2018-021860
|View full text |Cite
|
Sign up to set email alerts
|

Assessing C reactive protein/albumin ratio as a new biomarker for polycystic ovary syndrome: a case–control study of women from Bahraini medical clinics

Abstract: ObjectivePolycystic ovary syndrome (PCOS) is an endocrine disorder affecting approximately one in seven women who experience androgen excess, menstrual cycle irregularities, frequent anovulation and a tendency for central obesity and insulin resistance. Chronic subclinical inflammation is now recognised as being common in the context of PCOS, which led to the postulation that PCOS may fundamentally be an inflammatory process. This study aimed to: (1) evaluate serum C reactive protein (CRP)/albumin ratio as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Compared with controls, PCOS patients have increased CRP/albumin ratio irrespective of the BMI. 17 This finding supports the view that inflammation may be a central pathophysiologic player in PCOS, independent of BMI and adiposity.…”
Section: The Clinical Application Of High Crp In Pcossupporting
confidence: 82%
See 4 more Smart Citations
“…Compared with controls, PCOS patients have increased CRP/albumin ratio irrespective of the BMI. 17 This finding supports the view that inflammation may be a central pathophysiologic player in PCOS, independent of BMI and adiposity.…”
Section: The Clinical Application Of High Crp In Pcossupporting
confidence: 82%
“…These investigators have found that the CRP/albumin ratio had a higher specificity and sensitivity for inflammation associated with metabolic dysfunction than insulin resistance and androgens in matched PCOS patients. 17 Although none of our PCOS subjects 10 had any sign of inflammation, the higher erythrocyte sedimentation rate in the PCOS patients versus controls supports the study by Kelly et al 9 suggesting a chronic subclinical inflammatory process as an underlying mechanism of atherosclerosis in PCOS. 10,18 Visceral/abdominal fat distribution is independently associated with low-grade inflammation.…”
Section: The Clinical Application Of High Crp In Pcossupporting
confidence: 79%
See 3 more Smart Citations